Author Correction: Planar and van der Waals heterostructures for vertical tunnelling single electron transistors (Nature Communications, (2019), 10, 1, (230), 10.1038/s41467-018-08227-1) - Kim, G. (Nature Publishing Group, 2021)
10.1038/s41467-019-08910-x